2014
DOI: 10.2135/cropsci2014.03.0221
|View full text |Cite
|
Sign up to set email alerts
|

Forming Core Collections in Barnyard, Kodo, and Little Millets using Morphoagronomic Descriptors

Abstract: 2673ReseaRch M illets, which are comprised of a number of C 4 smallgrained, annual cereal grasses including barnyard millet, kodo millet, and little millet have abundant within-species racial diversity. These species also differ in ploidy levels. The ploidy levels in barnyard millet range from tetraploid to hexaploid to octaploid, while kodo and little millets are tetraploids (de Wet et al., 1983;Wanous, 1990). Barnyard millet has two distinct cultivated species, the Indian barnyard millet [E. colona (L.) Link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 39 publications
(50 reference statements)
1
60
0
Order By: Relevance
“…in). Therefore, this study selected a representative set of 200 kodo millet accessions from the 665 accessions conserved at the ICRISAT genebank using the cluster information that was used to constitute the kodo millet core collection (Upadhyaya et al, 2014), representing ?30% of entire collection, and 26, 37, and 48% of the races regularis, variabilis, and irregularis, respectively. Globally, >8000 germplasm accessions of kodo millet have been conserved in genebanks, and a majority are housed in India (Upadhyaya et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…in). Therefore, this study selected a representative set of 200 kodo millet accessions from the 665 accessions conserved at the ICRISAT genebank using the cluster information that was used to constitute the kodo millet core collection (Upadhyaya et al, 2014), representing ?30% of entire collection, and 26, 37, and 48% of the races regularis, variabilis, and irregularis, respectively. Globally, >8000 germplasm accessions of kodo millet have been conserved in genebanks, and a majority are housed in India (Upadhyaya et al, 2015).…”
mentioning
confidence: 99%
“…Neither is such information available for grain nutritional traits that could provide important insights to kodo millet researchers and prove useful in germplasm selection and multilocation testing, and even lead to their direct release as cultivars. Therefore, this study selected a representative set of 200 kodo millet accessions from the 665 accessions conserved at the ICRISAT genebank using the cluster information that was used to constitute the kodo millet core collection (Upadhyaya et al, 2014), representing ?30% of entire collection, and 26, 37, and 48% of the races regularis, variabilis, and irregularis, respectively. This study aimed to assess kodo millet germplasm for morphoagronomic and grain nutritional traits, to assess the association between agronomic and grain nutritional traits, and to identify high-yielding and nutrient-rich accessions for use in research to identify and/or develop suitable cultivars.…”
mentioning
confidence: 99%
“…For the past two decades, germplasm characterization at ICRISAT has led to the establishment of core and minicore collections for pearl millet (Bhattacharjee et al, 2007; Upadhyaya et al, 2009, 2011a), finger millet (Upadhyaya et al, 2006), and foxtail millet (Upadhyaya et al, 2008, 2011b) while only core collections was established for other small millets (Upadhyaya et al, 2014) ( Figure 1 ).…”
Section: Characterization Of Millet Germplasm For Grain Nutrientsmentioning
confidence: 99%
“…For optimum and precise utilization of diversity for agronomic and nutritional improvement, a core collection representing 50 and 89 accessions has been developed by Gowda et al () and Upadhyaya et al (), respectively. Halaswamy et al.…”
Section: Germplasm and Its Impactmentioning
confidence: 99%
“…For optimum and precise utilization of diversity for agronomic and nutritional improvement, a core collection representing 50 and 89 accessions has been developed by Gowda et al (2009) and Upadhyaya et al (2014), respectively. Halaswamy et al (2001) characterized the national collection and identified promising accessions for higher plant height (seven accessions), higher number of basal tillers (nine accessions), longer inflorescence (10 accessions) and early flowering (27 accessions).…”
Section: Germplasm and Its Impactmentioning
confidence: 99%